The stability of the global wheat trade in the post-soviet space: A trade duration approach - Tinoush Jamali Jaghdani; Thomas Glauben; Linde Johanna Götz; Miranda Svanidze; Sören Prehn (German Journal of Agricultural Economics (GJAE), 2024)
The collapse of the Soviet Union and the Iron Wall as well as the emergence of Kazakhstan, Russia, Ukraine and Romania as major actors on international grain markets since 2000 had increased the hope for a more stable international grain market. However, various short-run trade policy interventions of post-Soviet grain exporting countries during the 2000s and 2010s have caused temporary disruptions in global grain supply chains. Moreover, the growing number of protectionist state interventions and sanctions since the beginning of the 2010s, as well as growing geopolitical tensions, may also fragment global trade and thus threaten the stability of grain trade relations. Against this backdrop and given the current public and political debates about suitable "de-risking strategies" to stabilise international trade, this article aims to explore the stability of the global wheat trade in terms of the duration dependence of trade relations between the major grain exporters and their destinations from 2001 to 2021. We test whether there are differences between the relatively "new" post-Soviet exporters that have emerged and the "old" ones. Furthermore, we examine the correlation between the number of trade partners and the trade duration. We employ a discrete-time hazard model to annual trade data to estimate the baseline hazard and survival rate for eleven major wheat exporting countries. The results indicate that, by having overall duration dependence, no different pattern in trade stability can be identified between "new" and "old" actors, and initial indications suggest that having more trading partners favours the survival of trade relations.
Keywords: 330; Baseline Hazard; Global Wheat Supply Chain; Kaplan-Meier Estimator; Logit; Post-Soviet; Survival Rate; Trade Duration